Healing Hands, Inspiring Hearts: The Legacy of Dr. AN Chandrasekaran - Purna Bansal; Mahabaleshwar Mamadapur (Current Medical Issues)
Dr. AN Chandrasekaran is a pioneering figure in Indian medicine whose contributions have profoundly shaped the field of rheumatology. Born in 1938 in Ramayapet, Nizam State, his early life was influenced by a family rooted in education and public service. After excelling academically, he pursued an MBBS and MD at Madras Medical College and later specialized in rheumatology, receiving advanced training in the UK. Upon his return, he founded the first Department of Rheumatology in India at Madras Medical College in 1972, transforming it into a nationally recognized center for rheumatology treatment and research. Dr. Chandrasekaran’s work bridged the gap between Indian and Western medical approaches, and his pioneering research led to advancements in diagnostic tools and treatments for rheumatic diseases. In addition to his medical practice, he was instrumental in starting the DM Rheumatology program in 1991, training over 50 rheumatologists who continued his legacy across India. Beyond his medical achievements, Dr. Chandrasekaran’s humanitarian efforts have been far reaching. He has built schools, libraries, hospitals, and community infrastructure in rural Tamil Nadu, providing vital services to underserved populations. His ongoing free medical camps and efforts to improve maternal health have impacted thousands of lives. Recognized with numerous awards, including the Dr. BC Roy National Award and the Asia Pacific League of Associations for Rheumatology (APLAR) Master Award, Dr. Chandrasekaran’s contributions to medicine and society have earned him a reputation as a leader, educator, and humanitarian. His legacy inspires future generations of physicians and healthcare professionals, making him a deserving candidate for India’s prestigious Padma Bhushan Award.